2017
DOI: 10.1128/mbio.01370-17
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide Production by Chromobacterium piscinae Shields It from Bdellovibrio bacteriovorus HD100 Predation

Abstract: Predation of Chromobacterium piscinae by Bdellovibrio bacteriovorus HD100 was inhibited in dilute nutrient broth (DNB) but not in HEPES. Experiments showed that the effector responsible was present in the medium, as cell-free supernatants retained the ability to inhibit predation, and that the effector was not toxic to B. bacteriovorus. Violacein, a bisindole secondary metabolite produced by C. piscinae, was not responsible. Further characterization of C. piscinae found that this species produces sufficient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 56 publications
4
21
0
3
Order By: Relevance
“…Enhanced motilities with Leptospira interrogans (Berg and Turner, 1979) and Pseudomonas viscosa, Bacillus brevis or E. coli (Shoesmith, 1960) were also reported in other studies with methylcellulose and carrageenan. In the latter publication, the speed of E. coli increased by as much as 40% when the viscosity was 1.33 mPa s. Using 1% PEG here, we achieved a comparable increase (31%) in the average speed of B. bacteriovorus HD100, albeit at 5.4 mPa s. Based on the literature, the typical speed for this organism tends to fall between 20 and 50 μm s −1 (Lambert et al, 2006;Dwidar et al, 2015;Im et al, 2017;Mun et al, 2017), a range that includes the average measured here in HEPES-salt, i.e., 47.5 μm s −1 . However, in 1% PEG, several of the cells had speeds that surpassed 120 μm s −1 while the maximum speed recorded was 132 μm s −1 (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Enhanced motilities with Leptospira interrogans (Berg and Turner, 1979) and Pseudomonas viscosa, Bacillus brevis or E. coli (Shoesmith, 1960) were also reported in other studies with methylcellulose and carrageenan. In the latter publication, the speed of E. coli increased by as much as 40% when the viscosity was 1.33 mPa s. Using 1% PEG here, we achieved a comparable increase (31%) in the average speed of B. bacteriovorus HD100, albeit at 5.4 mPa s. Based on the literature, the typical speed for this organism tends to fall between 20 and 50 μm s −1 (Lambert et al, 2006;Dwidar et al, 2015;Im et al, 2017;Mun et al, 2017), a range that includes the average measured here in HEPES-salt, i.e., 47.5 μm s −1 . However, in 1% PEG, several of the cells had speeds that surpassed 120 μm s −1 while the maximum speed recorded was 132 μm s −1 (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies reported on a variety of environmental and biological factors that impact predation (Dwidar et al ., ; Im et al ., ; Mun et al ., ; Garcia et al ., ). More recently, Duncan et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations